Death in the shallows: The record of Permo-Triassic mass extinction in paralic settings, southwest China - Wignall, Paul B.; Chu, Daoliang; Hilton, Jason M.; Corso, Jacopo Dal; Wu, Yuyang; Wang, Yao; Atkinson, Jed; Tong, Jinnan (Global and planetary change, 2020)
The Permo-Triassic marine mass extinction has been blamed on a range of culprits including anoxia, acidification, high temperature and increased sedimentation and nutrient influx, the last two being a direct consequence of terrestrial biomass die-off and climatic changes. In marine settings, the role of these kill mechanisms is likely to be depth-dependent with siltation and high temperatures potentially the most consequential in shallowest waters. These ideas have been investigated in a study of the Permo-Triassic boundary beds in western Guizhou and eastern Yunnan (WGEY) which record the transition from littoral coal swamps to an inner shelf/platform fringed by a coastal mudbelt. Anoxic conditions were not developed in such shallow waters but weak dysoxia is seen in the extinction interval, recorded by the presence of pyrite framboids and glauconite, and may have been a factor in the crisis even in coastal waters. High temperatures may also be an extinction factor as evidenced by the brief bloom of microgastropods in the immediate aftermath. The Late Permian peat-forming swamps were subject to considerable in situ erosion that reworked authigenic minerals (chamosite and kaolinite). This material, together with considerable amounts of charcoal, was concentrated in distinctive green sandstone beds. However, the notion that the marine extinction was caused by increased sediment supply, a death-by-siltation mechanism following the collapse of terrestrial biomass, is not supported by the field evidence because a surge in clastic influx onto the shelf is not observed during the extinction interval when a range of carbonates, including microbialites, developed. The sediment was likely trapped in alluvial plains during base-level rise and/or a short period of more arid conditions occurred, reducing the clastic supply in the coastal–shallow marine environments. Ocean acidification is another potent kill mechanism but the occurrence of the extinction within a transgressive, carbonate-dominated interval in the shallow-water locations of WGEY does not support this cause. •This study examines the potential causes of the Permo-Triassic marine mass extinction using evidence from paralic outcrops in SW China.•It shows that widely cited ideas regarding the cause are unlikely to be tenable.•Thus, enhanced sediment run-off leading to siltation are not supported, neither is there strong evidence for ocean acidification.•Other causes such as marine anoxia appear more likely even in such remarkably shallow-water sections.